Effect of Material Smootheness and Concentration adhesive in Palm Oil solid Waste Briquette Making - Riswanti Sigalingging; Ainun Rohana (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Palm oil mill solid waste resulting from CPO production process is channeled into pond waste (Cooling Fond I). It is usually thrown to the ground so that it can contaminate the environment because it still contains waste oil. This study was aim to utilize the oil palm waste as briquettes. Briquettes is one of the alternative to replace oil. Research was done by completely randomized factorial design with 2 factors i.e : material fineness (20, 30, and 40 mesh) and adhesive  concentration (20, 30, and 40%). Parameters observed were calorific value,  heating time, oil volume, and sootness. The results showed that the material fineness had a highly significant effect on the caloric value, heating time, sootness and had no effect on the volume of oil. Adhesive concentration had a highly significant effect on the calorific value, heating time and had no effect on the volume of oil and sootness. The best treatment combination was K2P1 (thirty mesh material fineness and twenty percent adhesive concentration) with equipment caloric value of 18973,81 kal/gr, 56,57 minute heating time, and 2,25 gr sootness.